Color Grading pada Program Dokumenter Televisi “Indonesia dalam Realita” - Wikan Hadi Pamegat; Aprilina Dwi Astuti; Herry Abdul Hakim (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
In the world of television media, documentaries are a form of program that has an important role in conveying factual information to the audience. Color grading is the key to improving the visual quality of documentary programs. Color grading helps create an atmosphere that fits the theme, balances light, and increases visual interest. In observing several documentaries, it can be seen that image color is often a challenge, especially when taking pictures spontaneously. Deficiencies in the color aspect can reduce the visual appeal and clarity of the message to be conveyed. The aim of this research is to apply color grading to Indonesian documentary television programs in reality. This research uses a qualitative descriptive method, the research process goes through three stages, namely through three main stages of color grading, namely primary grading, secondary grading, and creative grading, using DaVinci Resolve 17 Studio software. The results of this research are that primary grading by adjusting the color space transform and primary wheels produces natural colors, secondary grading applied with custom curves, power windows, and blur produces a warm color display according to the artistic vision, while creative grading with the dehancer pro plugin produces a display which looks as if it was recorded using a roll of original Kodak film. Overall, the color grading process applied contributes to improving the visual quality and aesthetics of this documentary production.